2012
DOI: 10.1262/jrd.2012-046
|View full text |Cite
|
Sign up to set email alerts
|

Manual Rupture Versus Transvaginal Ultrasound-guided Aspiration of Allanto-amniotic Fluid in Multiple Pregnancies: A Clinical Approach to Embryo Reduction in Dairy Cattle

Abstract: Abstract.To avoid the problems associated with twinning in dairy cattle, one of the embryos may be eliminated. This study compares the effect on pregnancy maintenance of two embryo reduction techniques, manual rupture (MR) and transvaginal ultrasound-guided aspiration (TUGA) of allanto-amniotic fluid, in Holstein-Friesian cows with multiple pregnancies. In the first experiment, 61 lactating cows bearing unilateral twins (n=27), bilateral twins (n=30) or triplets/quadruplets (n=4) were subjected to MR (n=45) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The presence of a dead co-twin may be detected at the time of pregnancy diagnosis and its incidence could be as high as 16% [6]. Similar results have been obtained for the methods transvaginal allanto-amniotic fluid aspiration and manual amnion rupture [10,36]. Since the aspiration-based method is ultrasound guided and requires two people, we prefer to induce embryo reduction by manual rupture of the amniotic vesicle of bilateral and some unilateral twin pregnancies within our weekly visit program in controlling reproduction.…”
Section: Twin Reductionsupporting
confidence: 64%
“…The presence of a dead co-twin may be detected at the time of pregnancy diagnosis and its incidence could be as high as 16% [6]. Similar results have been obtained for the methods transvaginal allanto-amniotic fluid aspiration and manual amnion rupture [10,36]. Since the aspiration-based method is ultrasound guided and requires two people, we prefer to induce embryo reduction by manual rupture of the amniotic vesicle of bilateral and some unilateral twin pregnancies within our weekly visit program in controlling reproduction.…”
Section: Twin Reductionsupporting
confidence: 64%
“…Other proposed approaches to reduce twinning in cows on Days 28-41 of gestation consist of manual rupture of the amniotic vesicle and transvaginal ultrasound-guided aspiration of allanto-amniotic fluid or intra-luteal instillation of PGF2α in one of the two corpora lutea (López-Gatius, 2005;Andreu-Vázquez et al, 2012c;López-Gatius and Hunter, 2016). However, although inducing twin reduction avoids the negative effects of twinning, these interventions may increase the risk of pregnancy loss.…”
Section: Introductionmentioning
confidence: 99%
“…Although the results of this study did not result in a practical approach to decreasing DOV and twinning in lactating dairy cows, it did provide physiologic information that may focus future studies in this impor-tant area. Future studies may focus on reducing DOV through increasing circulating P4 during preovulatory follicle development using protocols such as Double-Ovsynch (Cunha et al, 2008;Wiltbank et al, 2012;Martins et al, 2018), genetic selection for reduced twinning or DOV (Lett and Kirkpatrick, 2018), aspiration of codominant follicles to increase likelihood of SOV (López-Gatius and Garcia-Ispierto, 2020), or use of embryo reduction (Hanrahan, 1983;Andreu-Vázquez et al, 2012b;. In regard to follicle aspiration, we have recently demonstrated that follicle aspiration can be used to reduce number of DF and ensure ovulation of a single DF in each ovary to increase bilateral twinning rates in beef cattle that are carriers for the high fecundity Trio allele (Madureira et al, 2020).…”
Section: Discussionmentioning
confidence: 99%